2017
DOI: 10.1002/ccd.27336
|View full text |Cite
|
Sign up to set email alerts
|

Does mild paravalvular regurgitation post transcatheter aortic valve implantation affect survival? A meta‐analysis

Abstract: Mild PVR was associated with increased all-cause and cardiovascular mortality after TAVI. Whether further interventions in mild PVR is of benefit, has yet to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 63 publications
0
36
1
2
Order By: Relevance
“…Experience with conventional valve replacement suggest that mild paravalvular regurgitation may be associated with hemolysis but has no detrimental effect on cardiac performance or mortality outcomes (19,21). However, more contemporary experience in the context of transcatheter valve implantation raises concerns that even mild paravalvular regurgitation may be detrimental to patient survival (22). We demonstrated that the mean gradient across SURD was 2.46 mmHg higher than the mean gradient across RDV.…”
Section: Discussionmentioning
confidence: 72%
“…Experience with conventional valve replacement suggest that mild paravalvular regurgitation may be associated with hemolysis but has no detrimental effect on cardiac performance or mortality outcomes (19,21). However, more contemporary experience in the context of transcatheter valve implantation raises concerns that even mild paravalvular regurgitation may be detrimental to patient survival (22). We demonstrated that the mean gradient across SURD was 2.46 mmHg higher than the mean gradient across RDV.…”
Section: Discussionmentioning
confidence: 72%
“…Despite impact of mild PVR on outcomes is discrepant among different studies, Ando et al demonstrated that even mild PVR is associated with increased mid‐term all‐cause and cardiovascular mortality after TAVI in a recent meta‐analysis . This finding highlights the need of an optimal performance of the implanted device to ensure an optimal long‐term outcome of the procedure itself .…”
Section: Discussionmentioning
confidence: 99%
“…Moderate or severe PVL is associated with intermediate and long-term morbidity and mortality 8,9 . Conflicting evidence exists regarding the impact of mild versus none to trivial PVL on mortality and morbidity 10,11 . Several factors might be of influence on these conflicting results.…”
Section: Glossary Of Abbreviationsmentioning
confidence: 99%